Effects of dietary macronutrient content on energy metabolism and uncoupling protein mRNA expression in broiler chickens - Collin, A.; Malheiros, R. D.; Moraes, VMB; Van As, P.; Darras, V. M.; Taouis, M.; Decuypere, E.; Buyse, J. (C A B I Publishing, 2003)
The objective of the present study was to investigate the effects of dietary macronutrient ratio on energy metabolism and on skeletal muscle mRNA expression of avian uncoupling protein (UCP), thought to be implicated in thermogenesis in birds. Broiler chickens from 2 to 6 weeks of age received one of three isoenergetic diets containing different macronutrient ratios (low-lipid (LL) 30 v. 77 g lipid/kg-, low-protein (LP) 125 v. 197 g crude protein (N X 6.25)/kg; low-carbohydrate (LC) 440 v. 520 g carbohydrate/kg). LP chickens were characterised by significantly lower body weights and food intakes compared with LL and LC chickens (-47 and -38% respectively) but similar heat production/kg metabolic body weight, as measured by indirect calorimetry, in the three groups. However, heat production/g food ingested was higher in animals receiving the LP diet (+41%, P<0.05). These chickens also deposited 57% less energy as protein (P<0.05) and 33% more as fat. No significant differences in energy and N balances were detected between LL and LC chickens. The diets with the higher fat contents (i.e. The LP and LC diets) induced slightly but significantly higher relative expressions of avian UCP mRNA in gastrocnemius muscle, measured by reverse transcription-polymerase chain reaction, than the LL diet (88 and 90 v. 78% glyceraldehyde-3-phosphate dehydrogenase respectively, P<0.05). Our present results are consistent with the recent view that UCP homologues could be involved in the regulation of lipid utilisation as fuel substrate and provide evidence that the macronutrient content of the diet regulates energy metabolism and especially protein and fat deposition.
Keywords: macronutrients; energy metabolism; uncoupling proteins; broiler chickens